FINE NEEDLE ASPIRATION CYTOLOGY (FNAC) IN DIAGNOSIS OF TUMORAL CALCINOSIS, A REPORT OF THREE CASES - Mohamedani, A. A.; ElSheik, Ahmed E.; Nugud, Faisal; Mohamed Osman, Osman Taha (Gezira Journal of Health Sciences, 2006)
Introduction: Tumoral calcinosis (T.C.) is very rare and generally of unknown aetiology characterized by calcific deposits in the soft tissues. Commonly seen in the second decade of life (reported age range 15 months to 83 years). We are reporting 3 cases of T. C. who were initially diagnosed by FNAC. Two of the 3 cases were female siblings who were referred to us as possible cases of recurrent fibrosarcomas following surgical excision. Case reports:  (1) Two female siblings aged 17 and 14 years  complaining of large swelling in the upper   outer right thigh and the left outer upper thigh around the hip joints respectively. There was no limitation of movement. The masses recurred within a short period after total excision. Neither specimen was subjected to histopathology. Clinical examination showed two masses each approximately 30cm maximum diameter and 10 cm width. In addition the younger sister showed an additional mass 4.5 cm in the outer aspect of her right elbow. (2) 18 months old female child, unrelated to the above two cases, presented with an egg-sized mass in the mid-lateral aspect of her right thigh  cystic and mobile.There is a history of quinine injection in the same area. No positive family history of a similar condition. All three cases showed normocalcaemia and hyperphosphataemia with specks of calcification on x - ray and cysts in ultrasound. FNAC showed structureless gung , calcium granules and inflammatory cells including foreign body type multinucleated giant cells. Histopathology confirmed the diagnosis of T. C. Discussion: Described the three types of T. C. (familial, idiopathic, and that in patients of chronic renal failure on dialysis). The differential diagnoses were also discussed as well as lines of management such as Ca ++ supplementation, phosphate restriction, acetazolamide, parathyroidectomy and the treatment of choice is total surgical excision. To our best knowledge this is the first time to report the use of fine needle aspiration cytology in the diagnosis of T. C. in Sudan.